DEVELOPMENT OF AIM/END-USE MODELS FOR SELECTING LOW CARBON TECHNOLOGY OPTIONS OF AMONIA PLANT By: Sarah Margaretha Sitorus NIM: 23017052 (Masterâs Program in Chemical Engineering) In the last few days, Indonesiaâs ammonia industry still used steam reforming of natural gas. However, this technology still has disadvantage for CO2 emissions. In addition, there is a plan from government to use coal become raw material for ammonia industry will increase CO2 emissions. It is necessary to reduce CO2 emissions in the ammonia industry sector by integrating alternative raw material with low carbon technology. In this study, a quantitative analysys was evaluated the unit process of ammonia industry to choose the optimum carbon mitigation from IPPU in Indonesiaâs ammonia industry by AIM/End-use model in 2010-2030. The model is built by baseline scenario and mitigations, which the differences of mitigation scenarios are promoting low carbon technology, Carbon Capture Storage (CCS) and used alternative raw material, such as coal and biomass. The results from analysys of each mitigation in the AIM/End-use model show that promotion of low carbon technology reduce IPPU emission 1,96 tons CO2e/tonne of ammonia. Where as promotion by coal gasification and Carbon Capture Storage (CCS) reduce IPPU emission 4,76 tons CO2/tonne of ammonia. On the other hand, alternative raw material, such as biomass reduce emission 5,49 tons CO2e/tonne of ammonia. Based on the results of ACC tools for optimum carbon tax 50 USD/tonCO2e, devined roadmap of selected technology with potential reduction optimal in every scenarios that was 5,8 million tons of CO2; 8,7 million tons of CO2e; 9 million tons of CO2e. Mitigation cost reduction in CM1 scenario is 216 millions USD, and mitigation cost additional in CM2 and CM3 scenarios are 22 millions USD and 48 millions USD. Notably, the promotion by substitution material and Carbon Capture Storage (CCS) is a main priority that must be considered for development of integrated and eco-friendly ammonia industry in the future. Keywords: ammonia industry, CO2 emission, IPPU, low carbon technology, AIM/End-use energy model - Margaretha M. R. Sitorus, Sarah
DEVELOPMENT OF AIM/END-USE MODELS FOR SELECTING LOW CARBON TECHNOLOGY OPTIONS OF AMONIA PLANT